(untitled) (Música Hodie, 2016)
This paper provides information on the creation of an original collection of music and imagery journeys based on the literature in oncology and palliative care. Background evidence is shared about music and relaxation, music relaxation in medical settings, and music and relaxation in oncology/hospice treatment. The development of the resource is illuminated with respect to principles that guided the design. The Journeys collection is a tool that can be used independently by persons experiencing a variety of issues including: anxiety, pain, stress, low self-esteem, and low mood, etcetera; as well as with groups when implemented by a healthcare professional. While the Journeys collection has been primarily developed for those receiving cancer care and palliative care, it has applications in a variety of settings for others in home, hospital, hospice, long-term care facilities and community centres; as well as for persons new to guided imagery and music. Keywords: Relaxation; Imagery; Guided imagery and music; Pain, Palliative care; Oncology.